Brazil Human Capital Review : Investing in People - World Bank (Washington, DC: World Bank, 2022)
How much talent is lost in Brazil because of unideal education and health conditions The Brazil Human Capital Review is part of the Human Capital Project, a global initiative of the World Bank Group that aims to raise attention on the importance of investing in people. Its focus relies on the conditions hindering children to flourish their potential labor productivity in Brazil. As a first step, this report proposes the Human Capital Index (HCI) to estimate the expected productivity of a child born today by the age of 18 when education and health conditions remain unaltered. Or simply, the HCI estimates the productivity level of the next generation of works. The results are alarming. How can Brazil recover from a decade lost in terms of human capital formation Mitigating the effects of the pandemic should be a priority. In the short-term, recommendations include: (a) adapt and strengthen policies already in place that have proven effects on human capital; (b) use the national conditional cash transfer program to support those more heavily affected by the pandemic; and (c) set as utmost priority a learning recovery and acceleration plan for the coming years.